Economic costs of reduced irrigation water availability in Uzbekistan (Central Asia) - Bekchanov, Maksud; Lamers, John P.A. (Springer, 2016)
Reduced river runoff and expected upstream infrastructural developments are both potential threats to irrigation water availability for the downstream countries in Central Asia. Although it has been recurrently mentioned that a reduction in water supply will hamper irrigation in the downstream countries, the magnitude of associated economic losses, economy-wide repercussions on employment rates, and degradation of irrigated lands has not been quantified as yet. A computable general equilibrium model is used to assess the economy-wide consequences of a reduced water supply in Uzbekistan—a country that encompasses more than half of the entire irrigated croplands in Central Asia. Modeling findings showed that a 10–20 % reduction in water supply, as expected in the near future, may reduce the areas to be irrigated by 241,000–374,000 hectares and may cause unemployment to a population of 712–868,000, resulting in a loss for the national income of 3.6–4.3 %. A series of technical, financial, and institutional measures, implementable at all levels starting from the farm to the basin scale, are discussed for reducing the expected water risks. The prospects of improving the basin-wide water management governance, increasing water and energy use efficiency, and establishing the necessary legal and institutional frameworks for enhancing the introduction of needed technological and socioeconomic change are argued as options for gaining more regional water security and equity.